Origins of the New International (Dis)order - M. Beeson (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The old international order created under the auspices of American hegemony in the aftermath of World War 2 appears to be unravelling. In part, this is a consequence of a redistribution of material power in the international system as other powers - especially China – seek to play a more prominent role. In part, however, it is a consequence of the actions of the Trump administration and its privileging of ‘America first’. Consequently, urgent challenges such as dealing with climate change, which seem to necessitate international cooperation, are likely to get worse and even more difficult to address. This paper details and analyses the range of ‘structural’ and agential forces that have collectively shaped the contemporary international order, but which are under increasing stress. Some of these factors— the relative of decline of the US, ‘the rise of the rest’, the persistence of authoritarianism— are familiar features of long-run historical change. What makes them significant in our time, I argue, is their potential to impede much needed international cooperation to address unambiguously collective challenges. Consequently, the new international disorder, threatens nothing less than the end of order of any sort—or any sort one might want to live under, at least.